?CHEMICAL KINETIC MODELLING STUDIES Part-I. The Reaction of Hydrogen Chloride with DI-Tertiary Butyl Peroxide - KHAN, M. ANWAR; BATT, L. (Biological Sciences - PJSIR, 1996)
The chemical kinetic modelling studies of the reaction of three torr of hydrogen chloride and one torr of di-t- butyl peroxide (dtBP) mixture was carried out, at 383°K, over a reaction time of 0-2500 seconds. The "Gear" programme was used to model this study. This modelling system assisted in choosing the reaction steps for a probable mecha- nism and in the assessment of rate parameters for individual steps in reaction mechanism.